“Ephraim is a Cake Not turned”: the Fruits of the False Knowledge of God According to Hos 7:8-16 - Balla, Ibolya (The Biblical Annals, 2022)
The document of the Pontifical Biblical Commission, called What is man? A Journey through Biblical Anthropology points out in Chapter 1 (“The Human being created by God”), par. 33 that “[t]he failure to recognise the ‘created’ nature of the human being is made explicit in history as an arrogant presumption…” (46) and in par. 34 that “[a]n extraordinary endowment of intelligence, wealth and power gives the human being the illusion of being equal to God. To expose this deception of conscience the Lord predicts the inglorious end of the arrogant” (47). Many of the critiques and prophecies of Hosea are proclaimed in a period of Israelite history which reflects false and arrogant presumptions of the people of God. During the reign of Jeroboam II (ca. 784–753 BC) Israel experienced economic growth, territorial expansion and peace with the Arameans and the Judeans. However, especially following the Syro-Ephraimite war (734–732 BC) it became clear that Israel’s political and military manoeuvres and his trust in his own strength can only lead to disaster. This is one of the recurring messages of Hosea who points out that the only way to stand is to believe and trust in God alone. Many of his images and concepts describe Israel’s false beliefs and presumptions which are based on the erroneous knowledge of God. Hos 7:8-16 can be read as an essence of this message. Its literary devices and notions emphasize that while Israel appears to be potent, he is in fact impotent, the undiscerning nation’s “strength” is withering away. Israel seems wise and knowledgeable when he is in fact unwise and does not know the way of life. In the context of the entire book this passage affirms that the basis of the relation of God and Israel is always the right knowledge of him which entails the right knowledge of the self and of its place in the universe. One of God’s greatest mercies for creation and Israel is that he is available, he can be sought, found and known through his words and deeds. Hosea as the mediator of God conveys to Israel that they can call upon God, seek him and know him. While his message is for a special historical period and circumstances, it is relevant for all ages when humans ignore their created nature and aspire to be powerful, self-sufficient, intelligent in economic, scientific, political and military matters.